Properties of nanoparticles ZnO:Mn immobilized in polyethylene matrix - Lashkarev, G.V.; Demydiuk, P.V.; Yurkov, G.Yu.; Dmitriev, O.I.; Bykov, O.I.; Klochkov, L.I.; Pyratinskiy, Y.P.; Slynko, E.I.; Khandozhko, A.G.; Popkov, O.V.; Taratanov, N.A. (Наноструктурное материаловедение, 2010)
Nanoparticles ZnO:Mn (3–5nm) immobilized in polyethylene matrix were synthesized. The samples with different content of the manganese (5, 10 and 20%) in the initial solution of the Mn and Zn precursors were investigated by means of ESR, PL and XRD. Thus the behavior of the Mn impurities in ZnO was studied. It was observed that most of the manganese in ZnO form second undefined phase MnOx or substitute the zinc in cation sublattice at the surface layer of the nanoparticles. The mean value of constant of hyperfine structure of Mn is higher than expected one ( = (94±3)·10⁻⁴ cm⁻¹) that is significantly differ from the constant of hyperfine structure of Mn incorporated into single crystal ZnO (76·10⁻⁴ cm⁻¹). Photoluminescence measurements has revealed wide band of emission in green-red region 500–600 nm, with different position of the maximum depending on the manganese content. Отримано наночастинки ZnO:Mn розміром 3–5 нм. За допо-могою методів ЕПР, рентгеноструктурного аналізу та фотолюмінесценції досліджували структуру цих наночастинок із вмістом марганцю 5, 10 і 20% щодо вихідного розчину пре-курсорів. Показано, що переважна кількість марганцю формує другу фазу та заміщує цинк у катіонній підрешітці вповерхневому прошарку цих наночастинок. Середнє значення константи надтонкої структури ( = (94±3)·10⁻⁴ см⁻¹),отримане методом ЕПР, виявилося більшим за очікуване та відмінним від довідникового для марганцю в кристалічній решітці ZnO (76·10⁻⁴ см⁻¹). Фотолюмінесцентні вимірювання виявили широку лінію випромінювання в зелено-червоній області спектра 500–600 нм із різним положенням максимуму залежно від типу зразка. Получены наночастицы ZnO:Mn размером 3–5 нм. С помощью методов ЭПР, рентгеноструктурного анализа и фотолюминесценции исследовалась структура этих наночастиц с содержанием марганца 5, 10 и 20% относительноисходного раствора прекурсоров. Показано, что преимущественное количество марганца формирует вторую фазу и замещает цинк в катионной подрешетке в поверхностномслое этих наночастиц. Среднее значение константы сверхтонкой структуры ( = (94±3)·10⁻⁴ cm⁻¹), полученное методомЭПР, оказалось большим по сравнению с ожидаемым и отличным от справочного для марганца в кристаллической решетке ZnO (76·10⁻⁴ см⁻¹). Фотолюминесцентные измерения выявили широкую линию излучения в зелено-красной области спектра 500600 нм с разным положением максимума в зависимости от типа образца.